Potensi Tumbuhan Jintan Hitam (Nigella sativa Linn.) sebagai Antihiperlipidemia - Lyan Nurlianti Lutfiah; Yani Lukmayani; Livia Syafnir (Bandung Conference Series: Pharmacy, 2024)
Abstract. Black cumin (Nigella sativa Linn.) is a plant that is useful as an antihyperlipidemic agent. Hyperlipidemia is a major risk factor for atherosclerosis. The research method used in this literature review is a literature search online databases. The results of the literature search indicate that black cumin has the potential as an antihyperlipidemic with the administration of extracts and essential oils. Absolute ethanol solvent and a mixture of methanol and distilled water are the best solvents. Between extracts and essential oils, extracts are proen to be more effective than essential oils. The antihyperlipidemic activity of black cumin (Nigella sativa Linn.) is influenced by the presence of compounds that function as antihyperlipidemic agents, specifically the terpenoid compound group and the active compound thymoquinone.Abstrak. Jintan hitam (Nigella sativa Linn.) merupakan salah satu tumbuhan yang bermanfaat sebagai antihiperlipidemia. Hiperlipidemia merupakan faktor risiko utama terjadinya aterosklerosis. Metode penelitian yang digunakan pada kajian pustaka ini adalah penelusuran pustaka melalui database online. Hasil penelusuran pustaka menunjukkan bahwa jintan hitam memiliki potensi sebagai antihiperlipidemia dengan pemberian ekstrak dan minyak atsiri. Pelarut etanol absolut serta campuran metanol dan aquadest merupakan pelarut yang terbaik. Antara ekstrak dengan minyak atsiri membuktikan bahwa ekstrak lebih efektif dibandingkan dengan minyak atsiri. Aktivitas antihiperlipidemia dari jintan hitam (Nigella sativa Linn.) dipengaruhi oleh adanya kandungan senyawa yang berfungsi sebagai agen antihiperlipidemia yaitu golongan senyawa terpenoid serta adanya senyawa aktif thymoquinone.